SINERGI PEMBINAAN KEWIRAUSAHAAN BAGI PEMUDA DI KABUPATEN SLEMAN - Endang Dwi Ratnasari; R. Widodo Triputro (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Entrepreneurship development for youth is crucial to welcoming the Golden Indonesia Era in 2045, ensuring that this era brings benefits in the form of increased national economic development. Youth are expected to contribute to the nation's economic independence. Capacity building through entrepreneurship development is carried out so that young people are no longer dependent on job providers but are instead able to become entrepreneurs. Entrepreneurship development for youth is certainly the responsibility of all parties, especially local governments through authorized regional apparatus. In 2024, Sleman Regency received the "Kabupaten Layak Wiramuda" or "Young Entrepreneur" award from the Ministry of Youth and Sports. This achievement demonstrates the local government's role in fostering entrepreneurship. However, youth entrepreneurship development still faces various challenges, such as limited skills, access to capital, unstable psychological conditions of young people, and a lack of ongoing mentoring. This study uses qualitative research methods to describe the synergy between several Regional Government Organizations (OPDs) in fostering entrepreneurship for young entrepreneurs. The aim is to analyze the synergy of entrepreneurship development for young people involving several regional government organizations (OPDs). The results of the study indicate that comprehensive synergy between Regional Government Organizations (OPDs) in fostering entrepreneurship for young people can increase the number of young entrepreneurs in Sleman Regency. This synergy in fostering entrepreneurship can provide more facilities for entrepreneurs, ranging from training, business permit services, even market access and business networks. Challenges in fostering entrepreneurship for young entrepreneurs include the clarity of the division of roles between Regional Government Organizations (OPDs) and the intensity of coordination. ABSTRAK Pembinaan kewirausahaan bagi pemuda penting dilakukan untuk menyongsong Indonesia Emas tahun 2045 agar era tersebut membawa keuntungan berupa kenaikan pembangunan ekonomi nasional. Pemuda diharapkan mampu berkontribusi dalam kemandirian ekonomi suatu bangsa. Peningkatan kapasitas berupa pembinaan kewirausahaan dilakukan agar pemuda tidak lagi tergantung pada penyedia pekerjaan, melainkan mampu berwirausaha. Pembinaan kewirausahaan bagi pemuda tentu menjadi tanggungjawab semua pihak, terutama pemerintah daerah melalui perangkat daerah yang berwenang. Tahun 2024 Kabupaten Sleman mendapatkan penghargaan Kabupaten Layak Wiramuda atau Wirausaha Muda oleh Kementerian Pemuda dan Olahraga, prestasi ini menjadi bukti bahwa pemerintah daerah telah berperan dalam pembinaan kewirausahaan tersebut. Namun, pengembangan kewirausahaan pemuda masih menghadapi berbagai tantangan, seperti keterbatasan keterampilan, akses permodalan, kondisi psikis pemuda yang belum stabil, serta kurangnya pendampingan berkelanjutan. Penelitian ini menggunakan metode penelitian kualitatif untuk menggambarkan sinergi beberapa Organisai Perangkat Daerah (OPD) dalam pembinaan kewirausahaan bagi wirausaha muda. Tujuannya untuk menganalisis sinergi pembinaan kewirausahaan bagi pemuda yang melibatkan beberapa organisasi pemerintah daerah (OPD). Hasil penelitian menunjukkan bahwa sinergi antar Organisai Perangkat Daerah (OPD) dalam pembinaan kewirausahaan bagi pemuda yang dilakukan secara komprehensif mampu meningkatkan jumlah wirausahawan muda di Kabupaten Sleman. Sinergi pembinaan kewirausahaan mampu memberikan fasilitasi lebih bagi para wirausahawan mulai dari pelatihan, pelayanan ijin berusaha, bahkan akses pasar dan jejaring usaha. Tantangan dari sinergi pembinaan kewiraushaan bagi wirausahawan muda yakni ketegasan dalam pembagian peran antar Organisai Perangkat Daerah (OPD dan keintensifan koordinasi.